Placenta accreta index as a predictor of placental invasion in cases of placenta previa - Ibrahim M El-Maghraby; Ahmed A Badr (Journal of Medicine in Scientific Research, 2022)
Objective This study aims to evaluate the role of the placenta accreta index in predicting placental invasion in patients with placenta previa. Patients and methods This study was carried on 60 pregnant women with placenta previa (after 30 weeks gestation). They were recruited from the Obstetrics and Gynecology clinic of Menoufia University hospitals and Shebin El Kom Teaching Hospital in the period from January 2019 to December 2020. Results Preterm labor was found in 15 (78.95%) patients in the accreta group and six (14.36%) patients in the nonaccreta group (P = 0.000). Hysterectomy was performed in 14 (73.68%) patients in the accreta group and four (9.76%) patients in the nonaccreta group (P = 0.000). Urological complications occurred in five (26.32%) patients in the accreta group and one (2.44%) patient in the nonaccreta group (P = 0.004). Blood transfusion was needed in 16 (84.21%) patients in the accreta group and seven (17.07%) patients in the nonaccreta group (P = 0.000). ICU transfer was needed in 10 (52.63%) patients in the accreta group and two (4.88%) patients in the nonaccreta group (P = 0.000). Conclusions Both grayscale and color Doppler ultrasound were very important in the prenatal diagnosis of placenta accreta to reduce maternal and perinatal mortality and morbidity, but color Doppler had higher sensitivity and specificity. Placenta accreta index score 4 can be used as a predictive cutoff value for prediction of placental invasion in patients with placenta previa. Placenta previa in current pregnancy, previous uterine scar, increased maternal age, number of dilation and curettage and number of pregnancies and labors, and the presence of previous history of placenta previa are all risk factors for placenta accreta, and placenta accreta is associated with increased postoperative morbidity. It is associated with increased blood loss, risk of blood transfusion, ICU admissions, wound sepsis, urological complications, and poor neonatal outcome.